"From pluri-activity to entrepreneurship: Swedish inshore commercial fisheries navigating in the service-oriented economy". Issue 4 (8th August 2021) - Andersson, Malin
ABSTRACT: For decades, inshore commercial fisheries of Sweden have declined in the number of fishermen. In parallel, the service economy has gained importance and the growth in tourism is one example. This implicates new conditions for small firms, active in traditional rural industries. While knowledge about the socio-cultural context of small tourism firms is underdeveloped and since policymaking assigns these firms a key role in sustainable rural development, this article aims to explore a traditional industry in change during the first decades of the twenty-first century. This qualitative study is based on a fieldwork inspired by multi-sited ethnography, conducted at the Swedish west coast for a dissertation published in 2019. Drawing on discourse theory and the concept of positioning, the analysis concludes that inshore fisheries in the service economy are expected to become sustainable entrepreneurs and hosts for their communities. The fishermen position themselves in a contradictory manner both resisting and conforming to the political management discourse. The contemporary service-oriented economy and social relations largely form these small firms, which are characterised by both a high dependency on authorities and by their encounters with harbour visitors.